Supporting Self-Regulated Learning in Distance Learning Contexts at Higher Education Level: Systematic Literature Review - Edisherashvili, Natalia; Saks, Katrin; Pedaste, Margus; Leijen, Äli (Frontiers in Psychology, 2022)
Lately, self-regulated learning (SRL) has assumed an even more important role in distance learning environments, with an unprecedented shift toward distance education during the COVID-19 pandemic. Distance education is expected to become a new normal in the post-COVID-19 era, especially at the higher education level, where, given that students are able to efficiently apply SRL strategies, academic success is attainable even in distant formats of instruction. The present study offers a systematic literature review providing an overview and systematic categorization of the interventions identified in the studies as supporting various areas of SRL in its various phases in distance education environments at the higher education levels. The results reveal that even though there are interventions for every area and phase of SRL, as complex and multi-component a process as SRL is, the need for an optimal combination of various interventions is pronounced. As revealed by the analysis, learner characteristics, their experience and the type of distance learning medium also need to be considered while choosing which intervention, with which technical design characteristics, and in which combinations to adopt while designing an SRL supportive distance learning environment. As for the gaps identified, emotion regulation seems to be vastly underexplored, and the preparatory and appraisal phases of the SRL cycle also need more attention.